(untitled) (Research, Society and Development, 2023)
Objective: To verify the effects of congenital syphilis on newborn hearing. Methods: Search for scientific articles in the Scielo, PUBMED, LILACS, Google Academic and Medline in Portuguese, available online in full, published in the last ten years. The research was carried out using the descriptors [(congenital syphilis) and (newborn)], [(congenital syphilis) and (developmental)], [(congenital syphilis) and (child hearing)], [(congenital syphilis) and (hearing health)] and [(congenital syphilis) and (hearing loss)]. Results: Five studies were found that answered the guiding question. The selected studies showed an association between congenital syphilis and hearing loss. The audiological findings suggest a slight electroacoustic alteration in the brainstem auditory evoked potentials, with a decrease in wave amplitude and delay in neural sound conduction when higher repetition rates of clicks per second were used. Conclusion: It was found that congenital syphilis has negative effects on the hearing of newborns and can be considered one of the risk indicators for hearing loss in this population.